Multispecies toxicity test for silver nanoparticles to derive hazardous concentration based on species sensitivity distribution for the protection of aquatic ecosystems. Issue 5 (27th May 2016) - Kwak, Jin Il; Cui, Rongxue; Nam, Sun-Hwa; Kim, Shin Woong; Chae, Yooeun; An, Youn-Joo
Abstract: With increasing concerns about the release of silver nanoparticles (AgNPs) into the environment and the risks they pose to ecological and human health, a number of studies of AgNP toxicity to aquatic organisms have been conducted. USEPA and EU JRC have published risk assessment reports for AgNPs. However, most previous studies have focused on the adverse effects of AgNPs on individual species. Hazardous concentration (HC) of AgNPs for protection of aquatic ecosystems that are based on species sensitivity distributions (SSDs) have not yet been derived because sufficient data have not been available. In this study, we conducted multispecies toxicity tests, including acute assays using eight species from five different taxonomic groups (bacteria, algae, flagellates, crustaceans and fish) and chronic assays using six species from four different taxonomic groups (algae, flagellates, crustaceans and fish). Using the results of these assays, we used a SSD approach to derive an AgNP aquatic HC5 (Hazard concentrations at the 5% species) of 0.614 μg/L. To our knowledge, this is the first report of a proposed HC of AgNPs for the protection of aquatic ecosystems that is based on SSDs and uses chronic toxicity data.